Activation of osteoblast ferroptosis by risperidone accelerates bone loss in mice models of schizophrenia - Hongyan Fan; Zaihong Yang; Lan Pang; Peifan Li; Changrong Duan; Guangyuan Xia; Lei Zheng (Journal of Orthopaedic Surgery and Research)
Abstract Background Ferroptosis is an iron-dependent regulatory cell death, which plays an essential role in bone loss. This study investigated whether the mechanism of risperidone (RIS)-induced bone loss is related to ferroptosis. Methods The schizophrenia mice were induced by administering MK-801. Subsequently, RIS were injected, or ferroptosis inhibitor Ferrostatin-1 (Fer-1) co-injected for 8 weeks. Bone loss of schizophrenia mice were assessed using microCT, H&E staining, ALP staining, ARS staining and WB, respectively. Ferroptosis of schizophrenia mice were detected by Iron Colorimetric Assay Kit and WB, respectively. In addition, ALP staining, ARS staining, and WB were performed to reveal the role of RIS in osteogenic differentiation of MC3T3-E1 and BMSCs cells. Results RIS treatment facilitates bone loss in schizophrenia mice and inhibit osteogenic differentiation of MC3T3-E1 and BMSCs cells. Moreover, up-regulated ferroptosis was found in vivo and in vitro after RIS treatment. Interesting, the bone loss and inhibition of osteogenic differentiation induced by RIS in schizophrenia mice were reversed by ferroptosis inhibitor Fer-1. Conclusion Ferroptosis induced by RIS aggravates the bone loss of schizophrenia mice via inhibiting osteogenic differentiation.